Answer:
44°
Explanation:
From the problem, we have two angles which sum results in a third one, that is:
![m\angle LKJ = m\angle LKC + m\angle CKJ](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2nnxyreeehili5qctvu29lpbyoinlnds2w.png)
So, using this relation, and replacing all expression into each angle, and then solving for x, we have:
![m\angle LKJ = m\angle LKC + m\angle CKJ\\131\°=x+96\°+x+53\°\\131\° - 96\° - 53\°=x+x\\-18=2x\\x=(-18)/(2)=-9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iix1ffngcjghrhrp10whms6cx59xrg51qc.png)
But, the problem is asking for the angle CKJ, so, replacing x by its value in the relation of this angle, we have:
![m\angle CKJ=x+53=-9+53\\m\angle CKJ=44\°](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qz8xkfrfk22q6vcyeivs8q4gf378fys8wg.png)
Therefore, the answer is 44°